When environmental legacy becomes a resource: On the making of secondary resources. Issue 101 (May 2019) - Bleicher, Alena; David, Martin; Rutjes, Henriette
Highlights: Resources from mining residues as option for diversifying critical mineral supply. Valorization of these materials is a prerequisite for becoming secondary resources. The understanding of mining residues as resource has to be culturally resonant. Expertise of scientists, everyday experience, mining history are important factors. Abstract: Recycling and extracting secondary resources from dumped materials has been considered as an option for generating a supply of critical minerals. Materials that are understood as secondary resources were already in use in society, but became devaluated and have been discarded as useless and worthless. In this article, we argue that the process of valorization that shifts material from the category of 'worthless' to the category of 'valuable' is a prerequisite for the making of secondary resources. We conceptualize valorization as a social process of framing in which the collective understanding of waste materials changes. Taking a frame theoretical approach, we aim to reveal how the understanding of waste materials as resources resonates culturally in two German case study regions. We will demonstrate that there are three features that influence the cultural resonance of this understanding quite differently in the two regions: the credibility of frame articulators, narrative fidelity and experiential commensurability. In one of the regions the resource frame is made culturally resonant through the acknowledged expertise of scientists and industries that tie in with the region's history and daily experiences, while in the other region, the resource frame is weakened due to bitter memories of historical developments and contested knowledge claims. By linking ideas from valorization studies with concepts from strategic framing, we are contributing to the scientific discourse regarding the production of secondary resources.